Bioinformatics as a Forensic Tool in Coronavirus Outbreak - Siraj Fakiha , Bandr (Journal of Indian Academy of Forensic Medicine, 2020)
The recent outbreak of the novel coronavirus has raised a lot of concerns on the effective strategies of diagnosing and managing such disease. As for governments and security agencies, the extent of the outbreak is a major concern regarding possible usage of bioweapons. As a result, a reflection on the existing forensic tools forms the basis of further research on the issue. Hence, an improvements on the application of bioinformatics in forensic investigations is a major area of concern for many medical and forensic researchers. This paper explores the advancements in bioinformatics as a forensic tool amid the developments in current novel coronavirus outbreak. Considering that there is limited resources to conduct a primary research on the novel coronavirus and the Covid-19 disease, a systematic review of the existing research is best suited for the research. Therefore, the research involves a review of the past research on bioinformatics and forensic investigations and its relations to the ongoing research on the novel coronavirus.